Living the interdiscipline: Natalie Alvarez speaks with Kim Solga about conceiving, developing, managing, and learning from a large-scale, multidisciplinary, scenario-based project supporting police de-escalation training in Ontario. Issue 3 (3rd July 2019) - Alvarez, Natalie; Solga, Kim
ABSTRACT: Ryerson University theatre professor Natalie Alvarez is currently helming a large, interdisciplinary team in southern Ontario that is testing the power of Forum Theatre to build better, more responsive scenarios for police officer training in de-escalation and mental crisis response. In this interview, Alvarez sits down with issue editor Kim Solga to talk about where this project came from, what challenges arise when working in an intensively interdisciplinary way – and how theatre and performance can serve effectively as a methodology at the heart of a wide range of scholarly investigations, both inside and outside of the arts and humanities.